2023
DOI: 10.1071/cp22065
|View full text |Cite
|
Sign up to set email alerts
|

Digital agriculture in Europe and in France: which organisations can boost adoption levels?

Abstract: This paper presents the way the digital transformation of the agricultural sector is implemented in Europe and in France. It describes the main European and national strategies, the structure of research and innovation initiatives, and the investment in capacity building to foster innovation, adoption and use. More specifically, the French research and innovation ecosystem on digital agriculture is described. The actors involved come from different organisations, such as research and higher educational institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…These develop technology applications based on a strong public science base, fostered through a strong concentric integration between actors within the agricultural system. This is the intended outcome of research policy in France and the EU to support digital agriculture (Bellon-Maurel et al 2023). The process is also implicit in the public-private partnerships reported for Australia (Hansen et al 2023;Lawes et al 2023) and in the digital agriculture start-ups observed in India (Goswami et al 2023).…”
Section: Crop and Pasture Sciencementioning
confidence: 92%
“…These develop technology applications based on a strong public science base, fostered through a strong concentric integration between actors within the agricultural system. This is the intended outcome of research policy in France and the EU to support digital agriculture (Bellon-Maurel et al 2023). The process is also implicit in the public-private partnerships reported for Australia (Hansen et al 2023;Lawes et al 2023) and in the digital agriculture start-ups observed in India (Goswami et al 2023).…”
Section: Crop and Pasture Sciencementioning
confidence: 92%
“…The beginning of the use of digital technologies in the agrifood sector can be considered as having appeared with the creation of web pages (Bellon-Maurel et al, 2023). It started by presenting information, before considering the dematerialization of declarations, such as those related to fertilization practices, or developing new distribution channels, such as online platforms.…”
Section: Introductionmentioning
confidence: 99%